2009
DOI: 10.1111/j.1365-2567.2009.03106.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal B‐cell activation associated with TALL‐1 over‐expression and SOCS‐1 suppression during chronic hepatitis C virus infection

Abstract: SummaryChronic hepatitis C virus (HCV) infection is associated with cirrhosis, autoimmunity and lymphoproliferative disorders. We have previously reported a differential regulation of T and B lymphocytes by HCV core protein in vitro. In this report, we employed a translational approach to characterize the activation status of peripheral B cells from individuals with chronic HCV infection and to explore potential mechanisms for B-cell dysregulation in the setting of HCV infection. In contrast to the T-cell supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 50 publications
0
32
0
1
Order By: Relevance
“…Another associated disease, known as non-Hodgkin lymphoma, results directly from aberrant B cell proliferation (70). As previously mentioned, SOCS1 is decreased in B cells taken from HCV-infected patients (39) or those incubated with HCV core protein in vitro (74). Decreased SOCS1 expression correlates with increased STAT1 activation and with increases in both B cell proliferation and IgM/IgG production.…”
Section: Effects Of Socs Expression On Viral Diseasementioning
confidence: 75%
See 1 more Smart Citation
“…Another associated disease, known as non-Hodgkin lymphoma, results directly from aberrant B cell proliferation (70). As previously mentioned, SOCS1 is decreased in B cells taken from HCV-infected patients (39) or those incubated with HCV core protein in vitro (74). Decreased SOCS1 expression correlates with increased STAT1 activation and with increases in both B cell proliferation and IgM/IgG production.…”
Section: Effects Of Socs Expression On Viral Diseasementioning
confidence: 75%
“…This is accompanied by decreases in STAT1 activation, markers of general T cell activation, and JAK/STAT-mediated IFN-␥ production, a response which greatly impedes the ability of CTLs to effectively clear viruses and promotes chronic HCV infection. In contrast, HCV core protein decreases the levels of SOCS1 in B cells (39,74). This decrease correlates with increased STAT1 activation and markers of general B cell activation, as well as increased B cell proliferation and antibody (IgM and IgG) production.…”
Section: Virally Exploited Functions Of Socs Proteinsmentioning
confidence: 94%
“…PD-1 and SOCS-1 were also shown to regulate murine monocyte IL-10/IL-12 production against bacterial infection (23)(24)(25)(26). Similarly, we demonstrated that HCV core protein, by interaction with a complement receptor (gC1qR), can differentially regulate T and B lymphocyte functions through modulating PD-1/SOCS-1 signaling (27)(28)(29)(30)(31)(32). Little is known about the role of these two negative modulators in human innate immune cells, such as M/M F s, in HCV infection.…”
mentioning
confidence: 80%
“…For detection of phosphorylated proteins, the membrane was probed with anti-phospho-STAT-1 (Tyr701), MAPK p38 (Thr 180/182), and total STAT or MAPK Ab (Cell Signaling Technology, Danvers, MA). The HRP secondary Ab incubation, signal development, and data process were carried out as described previously (28). HCV core/gC1qR or PD-1/PDL-1 blockade Primary M/M F s from healthy subjects or HCV patients or monocytic THP-1 cells were incubated with 10 ml anti-gC1qR (1:10 dilution, blocking Ab was generously provided by Dr. Young S. Hahn, University of Virginia), 10 mg/ml anti-PD1 or anti-PDL-1, or control IgG Abs (eBioscience, San Diego, CA) overnight, followed by stimulation with LPS and R848 in the presence or absence of HCV core protein for 18-72 h; IL-12/PD-1/SOCS-1 expression in the treated cells was detected as described.…”
Section: Western Blotting and Coimmunoprecipitationmentioning
confidence: 99%
“…HCV infection is associated not only with liver diseases, but also numerous hematologic, renal, dermatologic, rheumatic, and autoimmune disorders, including arthalgia, arthritis, vasculitis, Sicca syndrome, myalgia, and fibromyalgia (Buskila, 2009). The persistence of HCV in lymphocytes causes their oligoclonal and monoclonal proliferation, the appearance of non-organ-specific autoantibodies, and leads to autoimmune Type II mixed cryoglobulinemia and development of several types of indolent non-Hodgkin's lymphomas (de Re et al, 2009;Moorman et al, 2009;Atta et al, 2010).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%